A two-dimensional amide polymer-polyimide composite coating and a preparation method thereof
Patent Information
- Application Number
- CN202611170679.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对背景技术提出的问题,本发明的主要目的在于提出一种二维酰胺聚合物-聚酰亚胺复合涂层,二维酰胺聚合物的结构缺陷少并形成有序的二维骨架,且二维酰胺聚合物能够在聚酰亚胺基底的体系中更加均匀地分散,得到的二维酰胺聚合物-聚酰亚胺复合涂层的结构均匀致密、且防腐性能较高,解决了现有技术中单独应用二维酰胺聚合物作为防腐涂层时的独立成膜性不足,复合其他材料应用时二维酰胺聚合物难以在涂层中形成均匀的分布,获得的防腐涂层容易发生脆性开裂且防腐蚀性能较低的问题
本发明的二维酰胺聚合物-聚酰亚胺复合涂层通过将二维酰胺聚合物引入到含有酰胺键的聚酰亚胺基底中,并合理调控二维酰胺聚合物的添加量,有效削弱二维酰胺聚合物的二维片层结构之间原有的团聚趋势,使得二维酰胺聚合物能够在聚酰亚胺基底的体系中更加均匀地分散;二维酰胺聚合物通过引入氢化钙减少二维酰胺聚合物的结构缺陷并形成有序的二维骨架,降低二维酰胺聚合物-聚酰亚胺复合涂层出现脆性开裂的风险;通过充分利用二维酰胺聚合物独特的片层屏蔽效应与传质阻隔能力,并协同聚酰亚胺基底优良的耐热性、力学性能以及化学稳定性,协同提升复合涂层对于腐蚀介质的屏蔽性能,制备得到的二维酰胺聚合物-聚酰亚胺复合涂层的结构均匀致密、且防腐性能较高;解决了现有技术中,单独应用二维酰胺聚合物作为防腐涂层时的独立成膜性不足,复合其他材料应用时二维酰胺聚合物难以在涂层中形成均匀的分布,获得的防腐涂层容易发生脆性开裂且防腐蚀性能较低的问题。
Smart Images

Figure CN123004263A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a two-dimensional amide polymer-polyimide composite coating and its preparation method. Background Technology
[0002] Two-dimensional polymer materials are a class of two-dimensional organic polymers composed of structural units linked by in-plane covalent bonds. They combine the structural characteristics of two-dimensional materials (high specific surface area and layered structure, etc.) with the designability of polymer materials, demonstrating significant research value in fields such as separation, catalysis, sensing, and composite reinforcement. Among them, two-dimensional amide polymers are a novel type of two-dimensional polymer material that incorporates amide bonds into the two-dimensional polymer backbone. While maintaining the two-dimensional planar extension structure, they endow the material with higher backbone rigidity, excellent mechanical properties, and good barrier properties.
[0003] However, current research on the application of two-dimensional amide polymers mainly focuses on separation, adsorption, and catalysis, while the development of their application in corrosion prevention and isolation remains largely unexplored. Because two-dimensional amide polymers are prone to increased structural defects, local disorder, and lamellar overlap and aggregation during irreversible synthesis, their independent film-forming ability is insufficient when used alone as an anti-corrosion coating. When combined with other materials in the anti-corrosion coating, the two-dimensional amide polymer is difficult to form a uniform distribution in the coating. The numerous structural defects and local disorder also make the composite coating prone to brittle cracking, resulting in lower anti-corrosion performance. Summary of the Invention
[0004] In response to the problems raised in the background art, the main objective of this invention is to propose a two-dimensional amide polymer-polyimide composite coating. The two-dimensional amide polymer has fewer structural defects and forms an ordered two-dimensional skeleton. Furthermore, the two-dimensional amide polymer can be more uniformly dispersed in the polyimide substrate system. The resulting two-dimensional amide polymer-polyimide composite coating has a uniform and dense structure and high anti-corrosion performance. This solves the problems in the prior art where the two-dimensional amide polymer alone is insufficient in independent film formation when used as an anti-corrosion coating, and when combined with other materials, the two-dimensional amide polymer is difficult to form a uniform distribution in the coating, resulting in an anti-corrosion coating that is prone to brittle cracking and has low anti-corrosion performance.
[0005] Another objective of this invention is to provide a method for preparing a two-dimensional amide polymer-polyimide composite coating, which is used to prepare any of the above-mentioned two-dimensional amide polymer-polyimide composite coatings. The prepared two-dimensional amide polymer-polyimide composite coating has a uniform and dense structure and high corrosion resistance.
[0006] To achieve the above objectives, this invention proposes a two-dimensional amide polymer-polyimide composite coating, comprising the following raw materials: a polyimide substrate and a two-dimensional amide polymer; the raw materials for preparing the polyimide substrate include: 4,4'-diaminobenzoyl aniline, pyromellitic anhydride, and reaction solvent A; by weight percentage, the doping amount of the two-dimensional amide polymer is 1% to 9% of the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride, and the two-dimensional amide polymer; the raw materials for preparing the two-dimensional amide polymer include: melamine, 1,3,5-benzenetricarboxylic chloride, calcium hydride, and reaction solvent B.
[0007] Optionally, the doping amount of the two-dimensional amide polymer is 3% to 7% by weight of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride and the two-dimensional amide polymer.
[0008] Optionally, the molar ratio of the melamine, the 1,3,5-benzenetriformyl chloride, and the calcium hydride is 1:1:3.
[0009] Optionally, the reaction solvent A is one of N,N-dimethylacetamide or N,N-dimethylformamide.
[0010] Optionally, the reaction solvent B is a mixed solution of N-methyl-2-pyrrolidone and pyridine, wherein the volume ratio of N-methyl-2-pyrrolidone to pyridine is 9:1.
[0011] This invention also proposes a method for preparing a two-dimensional amide polymer-polyimide composite coating, used to prepare a two-dimensional amide polymer-polyimide composite coating as described in any one of the above claims. The method for preparing the two-dimensional amide polymer-polyimide composite coating includes the following steps: preparing a two-dimensional amide polymer: sequentially mixing melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride, adding reaction solvent B and stirring, reacting until the reaction system changes from liquid to colloid; washing, purifying, and drying the colloid to obtain a two-dimensional amide polymer powder; preparing a polyimide substrate: adding 4,4'-diaminobenzoyl aniline and reaction solvent A, stirring until the 4,4'-diaminobenzoyl aniline is obtained. 4'-Diaminobenzoyl aniline is dissolved, and pyromellitic anhydride is added and stirred continuously to obtain a polyimide base solution. The polyimide base solution and the two-dimensional amide polymer powder are mixed and stirred to obtain a two-dimensional amide polymer composite polyamic acid solution. The doping amount of the two-dimensional amide polymer is 1% to 9% by weight of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride and the two-dimensional amide polymer. The two-dimensional amide polymer composite polyamic acid solution is coated onto a metal substrate and then subjected to thermal imidization treatment. After cooling, a two-dimensional amide polymer-polyimide composite coating is prepared on the surface of the metal substrate.
[0012] Optionally, in the step of preparing the two-dimensional amide polymer, melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride are mixed sequentially and reaction solvent B is added. The mixture is then stirred at room temperature and pressure until the reaction system changes from a liquid to a colloid. The colloid is then washed and purified sequentially with anhydrous ethanol, deionized water and acetone to obtain a washed and purified intermediate product. The washing and purification steps involve sequentially performing water bath sonication, centrifugation and collecting the solid. The intermediate product is then dried to obtain the two-dimensional amide polymer powder.
[0013] Optionally, the solid content of the two-dimensional amide polymer composite polyamic acid solution is 10% by mass percentage.
[0014] Optionally, the step of thermal imidizing the metal substrate coated with the two-dimensional amide polymer composite polyamic acid solution includes: increasing the sintering temperature of thermal imidization from room temperature to 70, 100, 150, 250 and 300°C at a heating rate of 5°C / min, holding at each sintering temperature for 1 hour, and cooling to room temperature to obtain the two-dimensional amide polymer-polyimide composite coating on the surface of the metal substrate.
[0015] Optionally, before coating the two-dimensional amide polymer composite polyamic acid solution onto the metal substrate, the method further includes the following steps: cleaning, drying, and plasma treatment of the metal substrate.
[0016] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: The two-dimensional amide polymer-polyimide composite coating of this invention introduces a two-dimensional amide polymer into a polyimide substrate containing amide bonds and rationally controls the amount of two-dimensional amide polymer added. This effectively weakens the original agglomeration tendency between the two-dimensional sheet structures of the two-dimensional amide polymer, allowing the two-dimensional amide polymer to be more uniformly dispersed in the polyimide substrate system. By introducing calcium hydride into the two-dimensional amide polymer, structural defects of the two-dimensional amide polymer are reduced and an ordered two-dimensional skeleton is formed, reducing the risk of brittle cracking in the two-dimensional amide polymer-polyimide composite coating. By fully utilizing the unique sheet shielding effect and mass transfer barrier ability of the two-dimensional amide polymer, and synergistically combining it with the excellent heat resistance, mechanical properties, and chemical stability of the polyimide substrate, the shielding performance of the composite coating against corrosive media is synergistically improved. The resulting two-dimensional amide polymer-polyimide composite coating has a uniform and dense structure and high anti-corrosion performance. This solves the problems in the prior art where the independent film-forming ability of two-dimensional amide polymer is insufficient when used alone as an anti-corrosion coating, and the two-dimensional amide polymer is difficult to form a uniform distribution in the coating when combined with other materials, resulting in anti-corrosion coatings that are prone to brittle cracking and have low anti-corrosion performance. Attached Figure Description
[0017] Figure 1 This invention provides a pathway for the synthesis and thermal acylation of the polyimide substrate precursor in a two-dimensional amide polymer-polyimide composite coating, as described in one embodiment of the present invention. Figure 2 An optimized synthesis route for the two-dimensional amide polymer in a two-dimensional amide polymer-polyimide composite coating according to an embodiment of the present invention; Figure 3 This is a graph showing the test results of two-dimensional amide polymers A to C according to an embodiment of the present invention, wherein... Figure 3 (a) shows the infrared spectra of two-dimensional amide polymers A~C. Figure 3 (b) is a comparison diagram of the reference peak normalization results for two-dimensional amide polymers A to C; Figure 4 This is a hydrogen NMR spectrum of a two-dimensional amide polymer A according to an embodiment of the present invention; Figure 5 This is a diagram showing the single-molecule morphology and sheet size test results of a two-dimensional amide polymer A according to an embodiment of the present invention, wherein... Figure 5 (a) is a transmission electron microscope image of a two-dimensional amide polymer A according to an embodiment of the present invention. Figure 5 (b) is a graph showing the sheet diameter statistics of two-dimensional amide polymer A according to an embodiment of the present invention; Figure 6 This is a diagram showing the packing state and number of layers of a two-dimensional amide polymer A according to an embodiment of the present invention, wherein... Figure 6 (a) is an AFM height image of the two-dimensional amide polymer A. Figure 6 (b) is a cross-sectional height curve of the two-dimensional amide polymer A; Figure 7 This is a scanning electron microscope image of a two-dimensional amide polymer A according to an embodiment of the present invention; Figure 8 This is a temperature rise curve of the thermal imidization treatment of a two-dimensional amide polymer-polyimide composite coating according to an embodiment of the present invention; Figure 9 Infrared spectra of Examples 3, 6 and Comparative Example 1 of the two-dimensional amide polymer-polyimide composite coating of the present invention; Figure 10 These are scanning electron microscope (SEM) images of Comparative Example 1 and Examples 1-5 of the two-dimensional amide polymer-polyimide composite coating of the present invention, wherein... Figure 10 (a) ~ Figure 10 (f) Scanning electron microscope images of Comparative Example 1 and Examples 1 to 5, respectively; Figure 11 The thickness statistics of the two-dimensional amide polymer-polyimide composite coating of the present invention are shown in Comparative Example 1, Examples 1-2, and Examples 4-5. Figure 12 Comparative thermogravimetric data comparison chart of Comparative Examples 1, 3 and 6 of the two-dimensional amide polymer-polyimide composite coating of the present invention; Figure 13 The figures show the Tafel test results of the two-dimensional amide polymer-polyimide composite coating of the present invention in Comparative Example 1, Examples 1-6, and pure aluminum sheets using 100 ppm hydrofluoric acid as electrolyte. Figure 13 (a) is a Tafel polarization curve diagram of Comparative Example 1, Examples 1-6, and pure aluminum sheet. Figure 13 (b) is a graph showing the corrosion current density and corrosion potential of Comparative Example 1, Examples 1-6 and pure aluminum sheets; Figure 14 The figures show comparative examples 1, examples 1-6, and Tafel test results of pure aluminum sheets using 0.1 M sodium hydroxide as electrolyte for the two-dimensional amide polymer-polyimide composite coating of the present invention. Figure 14 (a) is a Tafel polarization curve diagram of Comparative Example 1, Examples 1-6, and pure aluminum sheet. Figure 14 (b) is a graph showing the corrosion current density and corrosion potential of Comparative Example 1, Examples 1-6 and pure aluminum sheets; Figure 15 The figures show comparative examples 1, examples 1-6, and Tafel test results of pure aluminum sheets using 0.1 M hydrogen chloride as the electrolyte for the two-dimensional amide polymer-polyimide composite coating of the present invention. Figure 15 (a) is a Tafel polarization curve diagram of Comparative Example 1, Examples 1-6, and pure aluminum sheet. Figure 15 (b) is a graph showing the corrosion current density and corrosion potential of Comparative Example 1, Examples 1-6 and pure aluminum sheets. Detailed Implementation
[0018] This invention proposes a two-dimensional amide polymer-polyimide composite coating, comprising the following raw materials: a polyimide substrate and a two-dimensional amide polymer; the raw materials for preparing the polyimide substrate include: 4,4'-diaminobenzoyl aniline (DABA), pyromellitic alkyl anhydride (PMDA), and reaction solvent A; The doping amount of the two-dimensional amide polymer is 1% to 9% by weight, which is the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride, and the two-dimensional amide polymer. The raw materials for preparing the two-dimensional amide polymer include: melamine, 1,3,5-benzenetricarboxyl chloride, calcium hydride, and reaction solvent B.
[0019] Specifically, the synthesis of the two-dimensional amide polymer depends on the polycondensation reaction between melamine and 1,3,5-benzenetricarboxyl chloride monomer. However, the existing reaction system for synthesizing two-dimensional amide polymers is sensitive to moisture, and the byproduct hydrogen chloride (HCl) generated during the reaction has an adverse effect on the polymerization process. HCl has strong acidity and can protonate the amino group in the melamine molecule, reducing the nucleophilicity of the amino group and thus weakening its ability to attack the carbonyl carbon of the acyl chloride, which is not conducive to the continuous formation of subsequent amide bonds. Furthermore, the presence of HCl acidifies the local reaction environment. In the presence of trace amounts of moisture in the system, it may further exacerbate the hydrolysis of acyl chloride groups, causing some of the active acyl chlorides that could have participated in the polycondensation reaction to transform into other inactive structures. This reduces the number of effective reaction sites, decreases the effective degree of polycondensation, and increases the residue of insufficiently reacted structures at the edges and defect sites of the sheets, affecting the chemical structural integrity of the product. This results in more structural defects and local disorder in the prepared two-dimensional amide polymer. At the same time, the strong hydrogen bonds and π–π interactions between the two-dimensional sheets easily lead to sheet overlap and aggregation, resulting in insufficient independent film-forming ability of the two-dimensional amide polymer when used alone as an anti-corrosion coating material. When used as a filler to prepare composite coatings, it is difficult to form a uniform distribution in the coating. The numerous structural defects and local disorder also make the composite coating prone to brittle cracking, reducing the anti-corrosion performance of the composite coating.
[0020] The two-dimensional amide polymer-polyimide composite coating of this invention, by introducing the two-dimensional amide polymer into a polyimide substrate containing amide bonds and rationally controlling the doping amount of the two-dimensional amide polymer, combines the barrier effect of the two-dimensional layered structure with the interfacial interaction capability imparted by the amide groups. Simultaneously, the high aspect ratio of the polyimide substrate extends the diffusion path of the corrosive medium, effectively improving the density of the two-dimensional amide polymer-polyimide composite coating. Furthermore, the raw materials for preparing the polyimide substrate include: 4,4'-diaminobenzoyl aniline (DABA), pyromellitic phthalic anhydride (PMDA), and reaction solvent A, which are then used to prepare the coating. The polyimide substrate is a DABA-PMDA type polyimide with amide bonds introduced into its molecular chain. The two-dimensional amide polymer backbone contains a large number of amide groups, which can form strong hydrogen bonds with the polyimide substrate containing amide bonds through NH…O=C. These hydrogen bonds improve the compatibility between the two-dimensional amide polymer and the polyimide substrate, weakening the original aggregation tendency between the two-dimensional sheet structures of the two-dimensional amide polymer. This allows the two-dimensional amide polymer to be more uniformly dispersed in the polyimide substrate system, resulting in a uniform and dense two-dimensional amide polymer-polyimide composite coating. The precursor synthesis and thermal amidation pathway of the polyimide substrate are as follows: Figure 1 As shown.
[0021] This invention introduces calcium hydride into the raw materials for preparing the two-dimensional amide polymer. Calcium hydride's strong water-absorbing capacity effectively removes trace amounts of moisture from the synthesis reaction system, providing a drier and more stable reaction environment for the polycondensation reaction. Furthermore, the calcium hydroxide formed after calcium hydride absorbs water effectively absorbs the hydrogen chloride byproduct produced in the reaction, reducing the structural instability caused by the byproduct and creating a more stable reaction environment for the ordered two-dimensional framework. Studies have shown that the introduction of calcium hydride significantly increases the relative content of amide bonds in the two-dimensional amide polymer synthesis reaction system, thus enhancing the formation of the target amide structure. This helps reduce structural defects in the two-dimensional amide polymer and form an ordered two-dimensional framework.
[0022] The two-dimensional amide polymer-polyimide composite coating of this invention effectively weakens the original agglomeration tendency between the two-dimensional sheet structures of the two-dimensional amide polymer by introducing the two-dimensional amide polymer into the polyimide substrate containing amide bonds and reasonably controlling the amount of the two-dimensional amide polymer added, so that the two-dimensional amide polymer can be more uniformly dispersed in the polyimide substrate system; the two-dimensional amide polymer is reduced by introducing calcium hydride to reduce structural defects and form an ordered two-dimensional skeleton, thereby reducing the risk of brittle cracking of the two-dimensional amide polymer-polyimide composite coating; through filling By utilizing the unique sheet-like shielding effect and mass transfer barrier capability of the two-dimensional amide polymer, and in conjunction with the excellent heat resistance, mechanical properties, and chemical stability of the polyimide substrate, the shielding performance of the composite coating against corrosive media is synergistically improved. This results in a uniform and dense structure and high corrosion resistance in the two-dimensional amide polymer-polyimide composite coating. This solves the problems in existing technologies where the two-dimensional amide polymer alone lacks independent film-forming ability when used as an anti-corrosion coating, and when combined with other materials, the two-dimensional amide polymer is difficult to form a uniform distribution in the coating, leading to brittle cracking and low corrosion resistance in the resulting anti-corrosion coating.
[0023] To further clarify, the doping amount of the two-dimensional amide polymer, by weight percentage, is 3% to 7% of the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride, and the two-dimensional amide polymer.
[0024] This invention significantly improves the corrosion resistance of the two-dimensional amide polymer-polyimide composite coating by introducing an appropriate amount of the two-dimensional amide polymer into the polyimide substrate containing amide bonds. This is primarily because the two-dimensional lamellar structure of the amide polymer forms more tortuous diffusion channels within the polyimide substrate, creating a pronounced "maze effect." This effectively prolongs the penetration path of water molecules, oxygen, and corrosive ions from the corrosive medium to the metal / coating interface, reducing the rate of corrosion reaction. Simultaneously, the high in-plane density and excellent shielding properties of the two-dimensional amide polymer itself also contribute to improving the overall density and interfacial barrier capability of the two-dimensional amide polymer-polyimide composite coating.
[0025] Under low doping conditions, the corrosion potential increases and the corrosion current density decreases, resulting in better corrosion resistance (corrosion current density reflects the kinetic rate of corrosion reaction on the metal surface: the lower the corrosion current density, the lower the corrosion rate and the better the corrosion resistance; corrosion potential mainly reflects the tendency of the material to corrode: a positive shift in the potential indicates a decrease in the tendency to corrode).
[0026] However, when the doping amount of the two-dimensional amide polymer is too high, the corrosion resistance of the two-dimensional amide polymer-polyimide composite coating decreases: because the high content of two-dimensional sheet structure makes it easier for the two-dimensional layer structure to agglomerate and locally stack in the polyimide substrate, the enhanced interlayer interaction weakens the uniform dispersion of the two-dimensional amide polymer in the matrix, resulting in uneven distribution of two-dimensional materials, local defects or loose structure inside the two-dimensional amide polymer-polyimide composite coating, leading to a decrease in corrosion resistance.
[0027] Furthermore, the optimal doping amount of the two-dimensional amide polymer is affected by the properties of the corrosive medium. The internal structural stability, corrosive medium penetration behavior, and interfacial reaction process of the two-dimensional amide polymer-polyimide composite coating vary under different acid and alkaline environments. Preferably, the doping amount of the two-dimensional amide polymer is set to 3%~7% of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride, and the two-dimensional amide polymer. Studies have confirmed that in Tafel polarization tests using 100 ppm hydrofluoric acid solution as the electrolyte, the optimal doping amount of the two-dimensional amide polymer at 5% provides the best overall anti-corrosion effect. When using 0.1 M HCl solution as the electrolyte, the optimal doping amount of the two-dimensional amide polymer is 7%, and when using 0.1 M NaOH solution as the electrolyte, the optimal doping amount is 3%.
[0028] To further clarify, the molar ratio of the melamine, the 1,3,5-benzenetriformyl chloride, and the calcium hydride is 1:1:3.
[0029] When the amount of calcium hydride added is insufficient, its effect on removing trace amounts of moisture in the system is limited, which is detrimental to maintaining a stable amidation reaction environment. When the amount of calcium hydride added is too high, it may increase the burden on subsequent washing and purification, and may introduce calcium hydroxide, calcium chloride, or other calcium-containing inorganic residues into the product, affecting the purity and dispersion state of the two-dimensional amide polymer. Specifically, the optimized synthetic route of the two-dimensional amide polymer is as follows: Figure 2 As shown.
[0030] To further clarify, the reaction solvent A is one of N,N-dimethylacetamide (DMAC) or N,N-dimethylformamide (DMF).
[0031] To further clarify, the reaction solvent B is a mixed solution of N-methyl-2-pyrrolidone and pyridine, and the volume ratio of N-methyl-2-pyrrolidone to pyridine is 9:1.
[0032] This invention also proposes a method for preparing a two-dimensional amide polymer-polyimide composite coating, used to prepare the two-dimensional amide polymer-polyimide composite coating as described in any one of the above claims, wherein the method for preparing the two-dimensional amide polymer-polyimide composite coating includes the following steps: Preparation of two-dimensional amide polymer: Melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride are mixed sequentially, reaction solvent B is added and stirred, and the reaction is carried out until the reaction system changes from liquid to colloidal; the colloidal substance is washed, purified and dried to obtain two-dimensional amide polymer powder; Preparation of polyimide substrate: Add 4,4'-diaminobenzoyl aniline (DABA) and reaction solvent A, stir until the 4,4'-diaminobenzoyl aniline dissolves, add pyromellitic anhydride (PMDA) and continue stirring to obtain polyimide substrate solution; The polyimide substrate solution and the two-dimensional amide polymer powder are mixed and stirred to obtain a two-dimensional amide polymer composite polyamic acid solution; the doping amount of the two-dimensional amide polymer is 1% to 9% by weight of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride and the two-dimensional amide polymer. The two-dimensional amide polymer composite polyamic acid solution was coated onto a metal substrate and then subjected to thermal imidization treatment. After cooling, a two-dimensional amide polymer-polyimide composite coating was prepared on the surface of the metal substrate.
[0033] More specifically, both the polyimide substrate and the two-dimensional amide polymer contain polar functional groups such as carbonyl groups, which can generate strong interfacial interactions with the oxide layer or hydroxylation sites on the surface of the metal substrate. This helps to improve the adhesion between the two-dimensional amide polymer-polyimide composite coating and the metal substrate, reduce the probability of micropores and debonding defects at the interface, and thus inhibit the rapid diffusion of corrosive media along the interface of the composite coating and the metal substrate. When the interfacial bonding is weak, moisture, oxygen, and chloride ions (Cl...)... - Corrosive media such as amide polymers are more likely to preferentially penetrate along the interface and further induce local corrosion. However, after the introduction of the two-dimensional amide polymer, the richer polar groups and stronger interfacial interactions in the entire composite system can improve the interfacial stability and help delay the corrosion initiation process.
[0034] The two-dimensional amide polymer-polyimide composite coating prepared by this invention effectively weakens the original agglomeration tendency between the two-dimensional sheet structures of the two-dimensional amide polymer by combining the two-dimensional amide polymer with the polyimide substrate containing amide bonds. This allows the two-dimensional amide polymer to be more uniformly dispersed in the polyimide substrate system, resulting in a dense and uniform two-dimensional amide polymer-polyimide composite coating. Furthermore, the introduction of calcium hydride to reduce structural defects in the two-dimensional amide polymer and form an ordered two-dimensional framework helps reduce the risk of brittle cracking in the two-dimensional amide polymer-polyimide composite coating. By fully utilizing the unique sheet-like shielding effect and mass transfer barrier capability of the two-dimensional amide polymer, and in conjunction with the excellent heat resistance, mechanical properties, and chemical stability of the polyimide substrate, the shielding performance of the composite coating against corrosive media is synergistically improved. This results in a composite coating with a uniform and dense structure and high corrosion resistance. This solves the problems in the prior art where the two-dimensional amide polymer alone, when used as an anti-corrosion coating, lacks independent film-forming ability, and when combined with other materials, the two-dimensional amide polymer is difficult to form a uniform distribution in the coating, leading to brittle cracking and low corrosion resistance.
[0035] To further explain, in the step of preparing the two-dimensional amide polymer, melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride are mixed sequentially and reaction solvent B is added. The mixture is then stirred at room temperature and pressure until the reaction system changes from a liquid to a colloid. The colloid was washed and purified sequentially with anhydrous ethanol, deionized water and acetone to obtain a washed and purified intermediate product. The washing and purification steps included sequentially performing water bath sonication, centrifugation and collecting the solid, and drying the intermediate product to obtain the two-dimensional amide polymer powder.
[0036] In one embodiment, in the preparation step of the two-dimensional amide polymer (the optimized synthetic route of the two-dimensional amide polymer is as follows): Figure 2 As shown in the figure, melamine, 1,3,5-benzenetriformyl chloride and calcium hydride were added sequentially to a glass bottle, followed by reaction solvent B (9 mL of N-methyl-2-pyrrolidone and 1 mL of pyridine). The mixture was stirred and reacted at room temperature and pressure for 16 hours, causing the reaction system to change from a liquid to a colloid. The colloid was then immersed in anhydrous ethanol and ultrasonically dispersed in a water bath for 30 minutes. The supernatant was removed by centrifugation at 4000 rpm for 15 minutes, and the solid was collected. The solid was then immersed in 80 mL of deionized water and 80 mL of acetone, and ultrasonically dispersed and centrifuged under the same conditions to obtain the final washed and purified intermediate product. The intermediate product was placed in a vacuum oven and dried at 100°C for 16 hours to finally obtain a light yellow solid powder (i.e., the two-dimensional amide polymer powder).
[0037] To further explain, in the step of preparing the polyimide substrate: after adding 4,4'-diaminobenzoyl aniline (DABA) and reaction solvent A, the mixture is stirred thoroughly at room temperature until the 4,4'-diaminobenzoyl aniline dissolves. Then, pyromellitic anhydride (PMDA) is added and stirring is continued for 12 hours to obtain the polyimide substrate solution.
[0038] To further clarify, the solid content of the two-dimensional amide polymer composite polyamic acid solution is 10% by mass percentage.
[0039] When the solid content of the two-dimensional amide polymer composite polyamic acid solution is too low, the film layer formed by a single coating is relatively thin, and edge shrinkage or incomplete coverage is likely to occur; when the solid content of the two-dimensional amide polymer composite polyamic acid solution is too high, the viscosity of the solution increases significantly, which is not conducive to the uniform dispersion of the two-dimensional sheets and the leveling of the coating. The formula for calculating the solid content of the two-dimensional amide polymer composite polyamic acid solution is as follows: ; Where, m DABA The amount of DABA added during the preparation of the polyimide substrate solution is m. PMDA The amount of PMDA added during the preparation of the polyimide substrate solution, m 反应溶剂A m is the amount of reaction solvent A added during the preparation of the polyimide substrate solution. 二维酰胺聚合物 The amount of the two-dimensional amide polymer added is [amount].
[0040] Furthermore, since the overall solid content in the two-dimensional amide polymer composite polyamic acid solution is 10%, by fixing the contents of 4,4'-diaminobenzoyl aniline and pyromellitic anhydride, and adjusting the contents of the two-dimensional amide polymer and the reaction solvent A, examples or comparative examples with different doping amounts of the two-dimensional amide polymer can be obtained.
[0041] To further explain, the step of thermally imidizing the metal substrate coated with the two-dimensional amide polymer composite polyamic acid solution includes: The sintering temperature of thermal imidization was increased sequentially from room temperature to 70, 100, 150, 250 and 300 °C at a heating rate of 5 °C / min. Each sintering temperature was held for 1 hour. After cooling to room temperature, the two-dimensional amide polymer-polyimide composite coating was prepared on the surface of the metal substrate.
[0042] The stepwise heating thermal imidization process allows the solvent and reaction-generated water in the two-dimensional amide polymer composite polyamic acid solution to gradually escape, and promotes the gradual dehydration and cyclization of polyamic acid to form polyimide. This reduces the risk of rapid escape of volatile components causing bubbles, pores and cracks, and is beneficial for forming a continuous, uniform and dense composite coating.
[0043] To further explain, before coating the two-dimensional amide polymer composite polyamic acid solution onto the metal substrate, the following steps are also included: cleaning, drying and plasma treatment of the metal substrate.
[0044] In one embodiment, the metal substrate is an aluminum sheet. Before coating with the two-dimensional amide polymer composite polyamic acid solution, the aluminum sheet is cut into a 10 cm × 10 cm square substrate. To remove impurities and oil from the surface of the aluminum sheet, it is cleaned sequentially with deionized water and ethanol, and then dried with compressed air. Subsequently, the dried aluminum sheet is placed in a plasma treatment machine for surface plasma treatment for 10 minutes to improve the activity of the aluminum sheet surface and the coating adhesion. The plasma-treated aluminum sheet is fixed on a spin coater, and an appropriate amount of the two-dimensional amide polymer composite polyamic acid solution is dropped onto the surface of the aluminum sheet. A film is formed by spin coating. The spin coating conditions are set to 2000 rpm for 1 minute to obtain a uniform two-dimensional amide polymer composite polyamic acid precursor coating covering the surface of the aluminum sheet. After thermal imidization and cooling, a two-dimensional amide polymer-polyimide composite coating is obtained.
[0045] To facilitate understanding of the present invention, a more complete description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0046] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0047] (I) Preparation of two-dimensional amide polymers: (1) Two-dimensional amide polymer A: The raw materials for preparing the two-dimensional amide polymer A include: melamine, 1,3,5-benzenetricarboxyl chloride, calcium hydride, and reaction solvent B (N-methyl-2-pyrrolidone and pyridine). The preparation method of the two-dimensional amide polymer A is as follows: 126 mg of melamine (1 mmol), 265 mg of 1,3,5-benzenetricarboxyl chloride (TMC, 1 mmol), and 126 mg of calcium hydride (3 mmol) were added sequentially to a glass bottle. Reaction solvent B (9 mL N-methyl-2-pyrrolidone and 1 mL pyridine) was added, and the mixture was stirred at room temperature and pressure for 16 h until the reaction system changed from a liquid to a colloid. The colloid was immersed in 80 mL of anhydrous ethanol and ultrasonically dispersed in a water bath for 30 min. After centrifugation at 4000 rpm for 15 min, the supernatant was removed. The centrifuged solid was then immersed sequentially in 80 mL of deionized water and 80 mL of acetone, and ultrasonically dispersed and centrifuged under the same conditions to obtain a washed and purified intermediate product. The obtained intermediate product was dried in a vacuum oven at 100 °C for 16 h to obtain two-dimensional amide polymer A powder.
[0048] (2) Two-dimensional amide polymers B~C: The difference between two-dimensional amide polymer B and two-dimensional amide polymer A is that two-dimensional amide polymer B does not contain calcium hydride, while the rest of the preparation method is the same as that of two-dimensional amide polymer A. The difference between two-dimensional amide polymer C and two-dimensional amide polymer A is that two-dimensional amide polymer C does not contain pyridine, while the rest of the preparation method is the same as that of two-dimensional amide polymer A. (3) Analysis of the structure of two-dimensional amide polymers A~C: ① Infrared spectroscopy analysis was performed on two-dimensional amide polymers A to C respectively (the test method was: the powder samples (two-dimensional amide polymers A to C) were measured using total attenuation reflectance (ATR) mode, with a scanning range of 500 to 4000 cm⁻¹). -1The resolution is 4 cm. -1 (The measurement involved 32 scans). For the test results, please refer to [link / reference]. Figure 3 : like Figure 3 As shown in (a), 1624 cm -1 A distinct absorption peak appears at 1534 cm⁻¹, corresponding to the C=O stretching vibration in the amide bond, which is typical of the amide I band; 1 The infrared absorption peaks at these points correspond to the NH bending vibration and CN stretching vibration in the amide bond, belonging to the amide II band. The appearance of the above characteristic absorption peaks indicates that the target amide bond has been successfully formed in the reaction system, demonstrating that the two-dimensional amide polymer structure has been effectively constructed.
[0049] Furthermore, since unreacted acyl chloride groups may exist at the edges and internal defect sites of the two-dimensional sheets of the two-dimensional amide polymer, these residual acyl chloride groups will further react with ethanol and be capped during subsequent ethanol washing. The reaction formula is as follows: Therefore, 1702 cm⁻¹ in the infrared spectrum -1 The absorption peak corresponds to the C=O stretching vibration of the carbonyl group after capping. The presence of this peak indicates that there are still a certain amount of incompletely reacted groups originating from edge or defect sites in the sample, which are transformed into the corresponding capped structure during post-processing.
[0050] Further demonstrating the promoting effect of calcium hydride introduction on the reaction process and reducing the influence of sample thickness or contact differences on infrared absorption intensity, this invention employs a reference peak normalization method to perform semi-quantitative analysis of the absorption peak intensity in the infrared spectrum: using the C=O stretching vibration peak in the amide bond (1624 cm⁻¹) as the reference peak. -1 The target amide bond structure was characterized by the C=O stretching vibration peak of the capped group (1702 cm⁻¹). -1 As a reference, the peak intensity ratio A between the two was calculated. 1624 / A 1702 The relative contents of amide bond groups under different reaction conditions were compared, and the results are shown in Table 1 below.
[0051] Table 1 Comparison of Reference Peak Normalized Data .
[0052] From the results in Table 1 and Figure 3 (b) It can be seen that the A of the two-dimensional amide polymer A 1624 / A 1702The ratio was 1.304, significantly higher than the reference condition (2D amide polymer B) before the introduction of calcium hydride (1.006) and the ratio (2D amide polymer C) with only calcium hydride added (0.984). This indicates that the relative content of amide bonds in the reaction system significantly increased after the introduction of calcium hydride. The results show that the additional introduction of calcium hydride can effectively improve the formation degree of the target amide structure, thus playing a positive role in promoting the synthesis reaction of 2D amide polymers. It should be noted that 1702 cm⁻¹... -1 The absolute intensity of the absorption peak cannot be directly used to determine the number of structural defects in the two-dimensional amide polymer. This invention uses the normalized ratio A between the amide bond characteristic peak and the capped carbonyl peak. 1624 / A 1702 Semi-quantitative comparisons showed that when calcium hydride and pyridine were added simultaneously, the proportion of the target amide structure relative to the end-capping structure in the two-dimensional amide polymer A was higher, indicating that the reaction conditions were favorable for increasing the relative degree of amide bond formation. Therefore, the proportion of defective or end-capping-related structures decreased relative to the already formed amide backbone, indirectly indicating that calcium hydride helps reduce the relative proportion of insufficiently reacted sites and improves the structural integrity of the two-dimensional amide backbone.
[0053] ② To further confirm the chemical structure of the two-dimensional amide polymer, the two-dimensional amide polymer A was characterized by 1H NMR spectroscopy (the test method was as follows: 6 mg of two-dimensional amide polymer A powder was placed in 0.6 ml of deuterated DMSO (deuterated dimethyl sulfoxide) and sonicated in a water bath until clear and transparent. The solution sample was then measured using a 400 MHz NMR spectrometer, with 64 scans). The results are as follows. Figure 4 As shown: Among them, the peak at chemical shift of 0 ppm is the internal standard peak of tetramethylsilane (TMS) added with deuterated dimethyl sulfoxide reagent, and the peak at chemical shift of 2.5 ppm is the solvent peak of the deuterated DMSO used. Regarding the two-dimensional amide polymer A product, the signal peak at 8.64 ppm originates from the hydrogen in the benzene ring skeleton of the two-dimensional amide polymer A (referring to the aromatic ring proton introduced by the 1,3,5-benzenetricarboxyl chloride structural unit in the two-dimensional amide polymer A), and the signal peaks at 4.39 ppm and 1.36 ppm are the ethoxy proton peaks introduced during ethanol quenching; while the amide N-H protons in the skeleton of the two-dimensional amide polymer A did not appear in the 1H NMR spectrum due to exchange broadening in the solvent system and the strong hydrogen bonding interactions in the two-dimensional polymer network. In addition, the signal peak at 7.45 ppm is attributed to pyridine hydrogen that was not completely removed in the reaction solvent system; the signal peak at 6.69 ppm is the raw material peak of melamine; and the signal peaks at 2.17 ppm and 1.89 ppm are the signal peaks of the solvent NMP involved in the reaction.
[0054] FTIR (infrared spectroscopy) results indicate that amide bonds were successfully formed. Combined with 1H NMR characterization and morphology characterization, this provides supplementary evidence for the formation of the two-dimensional amide polymer target material.
[0055] ③ Further analysis of the microstructure of the two-dimensional amide polymer A was conducted, and the testing methods included: Scanning electron microscopy (SEM) analysis: A small amount of two-dimensional amide polymer powder was attached to the stage with conductive adhesive, sputtered with gold at a current of 6 mA for 90 s, and then observed under a scanning electron microscope (SEM electron beam voltage is 5 kV).
[0056] Transmission electron microscopy (TEM) analysis: A small amount of two-dimensional amide polymer powder was placed in a glass bottle, and dimethyl sulfoxide was added to prepare a 0.1 mg / ml dispersion of the two-dimensional amide polymer. A small amount of the dispersion was dropped onto a TEM copper grid, dried under vacuum at 100°C for 12 hours, and then observed under a transmission electron microscope. Bright-field imaging mode was used for measurement, with an accelerating voltage of 200 kV. The diameter of at least 50 two-dimensional material samples was measured using ImageJ software.
[0057] Atomic force microscopy (AFM) analysis: A small amount of 0.1 mg / ml two-dimensional amide polymer dispersion was dropped onto a silicon wafer and spin-coated at 2000 rpm for 1 minute. The wafer was then vacuum-dried at 100 °C for 12 hours. After drying, the sample was observed and analyzed under an atomic force microscope. The probe model was ScanAsyst-Air, and the testing mode was ScanAsyst (based on Peak Force Tapping). Data processing and sample thickness were performed using NanoScope Analysis software.
[0058] Specifically, TEM was used to observe the morphology of two-dimensional amide polymer monomers and to count their sheet diameters; AFM was used to observe the packing state and number of layers of the two-dimensional polymer material; and SEM was used to observe the macroscopic packing morphology of the material. The test results are as follows: Figures 5-7 As shown: Among them, TEM characterization is as follows Figure 5 As shown in (a), the two-dimensional amide polymer A sample exhibits a small size and uniform dispersion. Since the two-dimensional amide polymer is mainly composed of light elements, its electron scattering ability is weak. Therefore, the overall contrast is low in TEM characterization, and the sheet outlines are relatively unclear. However, no large-area continuous stacking or agglomeration was observed, indicating that the prepared two-dimensional amide polymer A has good dispersibility. Statistical analysis of the nanosheet size in multiple TEM images of the two-dimensional amide polymer A yielded the following results: Figure 5As shown in (b), the average sheet diameter is 8.91 ± 2.31 nm, indicating that the obtained two-dimensional amide polymer A sample exhibits a nanoscale sheet structure, mainly composed of small-sized nanosheets with a relatively concentrated size distribution.
[0059] AFM image of two-dimensional amide polymer A as shown Figure 6 As shown in (a), the dispersed two-dimensional amide polymer exhibits a certain degree of agglomeration after being dropped onto the silicon wafer surface and then re-dried. This is mainly because the distance between the layers gradually decreases during solvent evaporation, and under the influence of interlayer interaction forces, the originally dispersed nanosheets re-stack and aggregate. Several relatively independent local sheet regions with low overlap were selected in the AFM image, and along... Figure 6 (a) The height profile analysis of the line segments marked 1, 2, 3, and 5 is shown in the figure. Figure 6 (b) The apparent height of the obtained sheets is 1.40 ± 0.19 nm, indicating that it belongs to a typical ultrathin nanosheet structure. It should be noted that the AFM results show that the prepared two-dimensional amide polymer A does not exist entirely in a monolayer state, but rather in a state of few-layer stacking, sheet overlap, or local folding. However, the AFM morphology alone cannot determine whether the two-dimensional amide polymer A is prone to aggregation or cluster formation in solution; this result only confirms that a few-layer two-dimensional amide polymer structure is formed in the two-dimensional amide polymer A.
[0060] The macroscopic morphology of the two-dimensional amide polymer A was further characterized using SEM, and the electron microscope images are shown below. Figure 7 As shown, the particle size of the two-dimensional amide polymer A powder ranges from 20 to 100 μm, and the overall surface of the particles is relatively rough. Further magnification reveals that the particle surface is not dense and flat, but rather composed of numerous overlapping wrinkled sheets and spiked protrusions, exhibiting localized cluster-like assembly characteristics, thus forming a distinct hierarchical rough structure. Combined TEM and AFM results confirm that these micron-sized particles are not single, dense entities, but rather macroscopic aggregates formed by the further stacking and agglomeration of numerous nanosheets. The combined characterization results from TEM, AFM, and SEM show that the prepared two-dimensional amide polymer A intrinsically possesses a nanosheet structure with a lateral dimension of approximately 9 nm and a thickness of 1.4 nm. In the dry and powder states, hydrogen bonding and π-π interlayer interactions between the amide groups cause stacking and agglomeration between the sheets, resulting in a three-dimensional agglomerated particle morphology under SEM.
[0061] (II) Examples 1-6 and Comparative Example 1: (1) Example 1: The two-dimensional amide polymer-polyimide composite coating includes the following raw materials: a polyimide substrate and a two-dimensional amide polymer (the two-dimensional amide polymer is the two-dimensional amide polymer A prepared above); the raw materials for preparing the polyimide substrate include: 4,4'-diaminobenzoyl aniline (DABA), pyromellitic anhydride (PMDA) and reaction solvent A (N,N-dimethylacetamide); by weight percentage, the doping amount of the two-dimensional amide polymer A is 1% of the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride and the two-dimensional amide polymer A.
[0062] The preparation method of Example 1 is as follows: Preparation of polyimide substrate: 2.3 g of 4,4'-diaminobenzoyl aniline (DABA) and 40.9 g of reaction solvent A (N,N-dimethylacetamide DMAC) were added and stirred until the 4,4'-diaminobenzoyl aniline dissolved. 2.2 g of pyromellitic anhydride (PMDA) was added and stirring was continued for 12 h to obtain a polyimide substrate solution. The obtained polyimide substrate solution was mixed with 45 mg of the two-dimensional amide polymer A powder and stirred for 12 h to obtain a two-dimensional amide polymer composite polyamic acid solution (the solid content of the two-dimensional amide polymer composite polyamic acid solution was 10%). By weight percentage, the doping amount of the two-dimensional amide polymer A at this time was 1% of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride, and two-dimensional amide polymer A. The metal substrate (aluminum sheet) was cut into 10 cm × 10 cm square pieces and cleaned sequentially with deionized water and ethanol. After cleaning, it was dried with compressed air. Subsequently, the dried metal substrate (aluminum sheet) was placed in a plasma treatment machine for surface plasma treatment for 10 minutes. The plasma-treated metal substrate (aluminum sheet) was then fixed on a spin coater, and an appropriate amount of the two-dimensional amide polymer composite polyamic acid solution was dropped onto the surface of the metal substrate (aluminum sheet). A film was then formed using a spin coating method. The spin coating conditions were set to 2000 rpm for 1 min. The spin-coated metal substrate (aluminum sheet) sample was placed in a muffle furnace for stepwise thermal imidization treatment: the sintering temperature of thermal imidization was increased sequentially from room temperature to 70, 100, 150, 250, and 300 °C at a heating rate of 5 °C / min, and held at each sintering temperature for 1 h. After the heat treatment, the sample was allowed to cool naturally to room temperature with the furnace, thus obtaining the two-dimensional amide polymer-polyimide composite coating on the surface of the metal substrate. The heating curve of the thermal imidization treatment is shown below. Figure 8 As shown.
[0063] (2) Examples 2-6 and Comparative Example 1: Examples 2-6 and Comparative Example 1 differ from Example 1 in that the amounts of DABA, PMDA, DMAC, and two-dimensional amide polymer A are different, in order to prepare examples or comparative examples with different doping amounts of two-dimensional amide polymer A. The amounts of DABA, PMDA, DMAC, and two-dimensional amide polymer A added in Examples 2-6 and Comparative Example 1 are shown in Table 2 below: Table 2. Addition amounts of DABA, PMDA, DMAC, and two-dimensional amide polymer A .
[0064] (3) Morphological characterization test and corrosion prevention mechanism analysis: ① Fourier transform infrared spectroscopy was used (the test method was as follows: the solid powder was directly measured using the total attenuation reflectance (ATR) mode of the infrared spectrometer, with 32 scans per measurement and a resolution of 4 cm⁻¹). -1 The scanning range is 500 to 4000 cm. -1 The structural information of the two-dimensional amide polymer-polyimide composite coating was obtained by analyzing Example 3 (5% doping of two-dimensional amide polymer A), Comparative Example 1 (no addition of two-dimensional amide polymer A), and Example 6 (15% doping of two-dimensional amide polymer A). The test results are as follows. Figure 9 As shown: Comparative Example 1 at 1724 cm -1 The absorption peak at 1379 cm⁻¹ can be attributed to the C=O stretching vibration in the polyimide ring; -1 The absorption peak can be attributed to the CN stretching vibration in the imide structure, confirming the existence of the imide ring structure. When the two-dimensional amide polymer A is doped at a low concentration (Example 3), no obvious new characteristic peaks or peak position changes are observed in the infrared spectrum, indicating that the introduction of low-content two-dimensional amide polymer A does not significantly alter the chemical structure of the polyimide or its local chemical environment. When the doping concentration of two-dimensional amide polymer A is increased to 15% (Example 6), the absorption peak at 1724 cm⁻¹... -1 and 1379 cm -1Both characteristic peaks exhibited varying degrees of low wavenumber shift, indicating a stronger interfacial interaction between the two-dimensional amide polymer A and the polyimide substrate. This redshift phenomenon may originate from hydrogen bonding and dipole-dipole interactions between the amide groups in the two-dimensional amide polymer A and the imide groups in the polyimide substrate, thereby altering the electron cloud distribution and vibrational environment of the C=O and CN bonds in the polyimide molecular chain. Therefore, the above results demonstrate that the introduction of the two-dimensional amide polymer A did not alter the bulk chemical structure of the polyimide substrate. Furthermore, higher doping levels of the two-dimensional amide polymer A enable more pronounced interfacial interactions with the polyimide substrate, laying the foundation for constructing a structurally stable and well-bonded two-dimensional amide polymer-polyimide composite coating.
[0065] ② To further investigate the influence of the introduction of the two-dimensional amide polymer on the microstructure of the two-dimensional amide polymer-polyimide composite coating, SEM characterization (test method: aluminum sheets covered with the coating material were cut into small pieces of approximately 0.5 cm × 0.5 cm, adhered to the stage with conductive adhesive, sputtered with gold at 6 mA for 90 s, and then observed under a scanning electron microscope with an electron beam voltage of 5 kV) and coating thickness testing (test method: coating thickness was tested using a profilometer, with a probe movement distance of 500 μm and a movement speed of 50 μm / s) were performed. By comparing the surface and cross-sectional morphology, film uniformity, and thickness changes of Examples 1-5 and Comparative Example 1, the dispersion of the two-dimensional amide polymer in the polyimide substrate and the regulatory effect of the two-dimensional amide polymer on the integrity and density of the composite coating were further analyzed. The SEM characterization results are as follows: Figure 10 As shown: The surface of the pure polyimide coating in Comparative Example 1 is relatively continuous and dense, and no cracks were observed, indicating that the polyimide substrate has good film-forming properties. However, the surface of Comparative Example 1 is not completely smooth and has obvious undulations and wrinkles. This is because during the solvent evaporation process, the viscosity of the reaction system gradually increases, and the polymer chain segments will become entangled and accumulated, which can easily cause the liquid film to flow insufficiently in local areas, thus causing certain undulations and wrinkles to form on the surface of the coating.
[0066] When 1% by mass of two-dimensional amide polymer A was doped into the polyimide substrate, the surface morphology of the two-dimensional amide polymer-polyimide composite coating was improved, with a significant reduction in surface wrinkles and micro-undulations, indicating that the two-dimensional amide polymer can improve the film uniformity and surface continuity of the composite coating. At lower doping levels, the two-dimensional amide polymer can be relatively uniformly dispersed in the polyimide substrate. The high specific surface area and layered structure of the two-dimensional amide polymer help enhance the interfacial interaction between the polymer chains and the polyimide substrate, thereby limiting the entanglement and accumulation of polymer chain segments during solvent evaporation, reducing local stress concentration, and making the shrinkage within the system more uniform during film formation. When the doping mass fraction of the two-dimensional amide polymer material was increased to 3% and 7%, the surface of the two-dimensional amide polymer-polyimide composite coating could still maintain a relatively continuous and relatively flat state, with good surface uniformity and no obvious cracks or large-area agglomeration observed. When the doping amount of the two-dimensional amide polymer was 7%, a small number of local granular protrusions appeared on the sample surface, indicating that as the doping amount increased, the two-dimensional amide polymer A began to undergo a certain degree of local aggregation, but it did not significantly damage the overall continuity of the coating.
[0067] To further explain, although the two-dimensional amide polymer A has a three-dimensional aggregated particle morphology in the powder state (see [reference]), Figure 7 However, when its low concentration is combined with a polyimide substrate containing amide bonds, the surface of the prepared two-dimensional amide polymer-polyimide composite coating is relatively smooth, and no aggregation of the two-dimensional amide polymer is observed. This is because the two-dimensional amide polymer contains a large number of amide groups, which can form strong hydrogen bonds with DABA-PMDA type polyimide through NH…O=C. The hydrogen bond can improve the compatibility between the two-dimensional amide polymer and the polyimide substrate, weaken the original aggregation tendency of the two-dimensional amide polymer sheets, and make it more uniformly dispersed in the polyimide substrate system, thereby preparing a more uniform and dense two-dimensional amide polymer-polyimide composite coating.
[0068] When the doping mass fraction of the two-dimensional amide polymer A continues to increase to 7% or higher, due to the aggregation effect of high-content two-dimensional amide polymer in the polyimide substrate, a small amount of particulate agglomerates will appear on the surface of the two-dimensional amide polymer-polyimide composite coating, and the roughness will continue to increase. Because the two-dimensional amide polymer has a large specific surface area and strong interlayer interactions, at higher doping concentrations, the layers are more likely to recombine and agglomerate through van der Waals forces, hydrogen bonding, or interfacial attraction, leading to a decrease in its dispersion stability in the polyimide solution. Simultaneously, as the content of the two-dimensional amide polymer increases, the viscosity of the reaction system increases, and the synergistic flow capability between polymer segments and two-dimensional layers weakens, which also weakens the film-forming performance of the liquid film during spin coating, making it easier for filler-rich areas and microscopic protrusion structures to form in localized areas.
[0069] Further reading Figure 11 As can be seen from the thickness statistics chart, the thickness of the pure polyimide coating in Comparative Example 1 is 1.61 ± 0.55 μm. After adding two-dimensional amide polymer doping, the coating thickness shows a decreasing trend with the increase of doping mass fraction. Among them, the composite coating thickness of Example 2 (doping amount of 3%) and Example 4 (doping amount of 7%) is about 500 nm, and the composite coating thickness of Example 5 (doping amount of 9%) is further reduced.
[0070] Combining the SEM images and film thickness test results of the two-dimensional amide polymer-polyimide composite coating, it can be seen that the two-dimensional amide polymer-polyimide composite coating has good overall film-forming properties and structural integrity. The addition of an appropriate amount of two-dimensional amide polymer did not significantly disrupt the continuity of the film; on the contrary, it helped optimize the internal structure of the composite coating, making it more uniform and dense. The thickness of the composite coating is significantly lower than that of the pure polyimide coating, but the corrosion current density is lower, indicating that the improvement in its anti-corrosion performance is not due to the increase in film thickness. At the same time, the thicknesses of Examples 2 and 4 are relatively close, indicating that the subsequent differences in anti-corrosion performance mainly come from the regulation of the microstructure and interface characteristics of the composite coating after the introduction of the two-dimensional amide polymer, rather than simply from the change in the thickness of the composite coating.
[0071] ③ To further investigate the effect of introducing the two-dimensional amide polymer on the thermal stability of the composite system, thermogravimetric analysis was performed on Examples 3, 6, and Comparative Example 1 (test method: thermogravimetric analyzer with alumina crucible, measurement was performed under nitrogen atmosphere, test temperature range from room temperature to 800 °C, heating rate was 10 °C / min), the results are shown in […]. Figure 12 And Table 3, where T 5% and T 10% These represent the temperatures at which the cumulative mass loss of the sample reaches 5% and 10% of its initial mass during the thermogravimetric test, respectively: Table 3. Thermogravimetric data of Examples 3, 6 and Comparative Example 1 .
[0072] With increasing doping concentration of the two-dimensional amide polymer, the overall thermal stability of the composite system showed a decreasing trend, with the most significant decrease observed at a doping concentration of 15% (Example 6). Specifically, in Comparative Example 1 without doping with the two-dimensional amide polymer, T5% and T10% were 543°C and 579°C, respectively, while in Example 3 (with a two-dimensional amide polymer doping concentration of 5%), these values decreased to 514°C and 571°C, respectively, showing a smaller decrease. When the doping concentration of the two-dimensional amide polymer was further increased to 15% (Example 6), T5% and T10% decreased significantly to 351°C and 493°C, indicating that the two-dimensional amide polymer-polyimide composite coating had already begun to exhibit more significant weight loss behavior at lower temperatures. Simultaneously, the initial decomposition temperature also gradually decreased from 558°C in Comparative Example 1 to 548°C and 528°C, further demonstrating that the introduction of excessive two-dimensional amide polymer weakens the initial thermal decomposition stability of the composite system.
[0073] Therefore, the doping level of two-dimensional amide polymers has a significant impact on the thermal stability of the composite system. With low doping, the intrinsic heat-resistant framework of the polyimide substrate is maintained. However, under high doping conditions, the synergistic effect of the thermal instability of amide bonds and interfacial defects leads to a significant forward shift in the thermal degradation window. Appropriate doping can achieve functional regulation while preserving the intrinsic heat resistance of the polyimide substrate as much as possible, while excessive doping will hinder the improvement of the material's overall performance due to insufficient thermal stability and increased structural defects.
[0074] ④ To further test the corrosion resistance of the two-dimensional amide polymer-polyimide composite coating in various environments, Tafel polarization tests were performed on Examples 1-6, Comparative Example 1, and a pure aluminum sheet (denoted as Al) without any coating. The corrosion resistance of the coating material was reflected by the corrosion current density and corrosion potential.
[0075] The electrochemical testing (Tafel polarization test) method is as follows: A small piece of pure aluminum sheet or aluminum sheet coated with a material, approximately 1 cm × 1.3 cm in size, is cut. Insulating tape is used to cover the uncoated side of the aluminum sheet, leaving the coated side exposed to form the working electrode. A three-electrode system is constructed, using an Ag / AgCl electrode as the reference electrode (RE), a graphite electrode as the auxiliary electrode (CE), and a test electrode as the working electrode (WE). This system is then inserted into the electrolyte and connected to an electrochemical workstation for testing. Before testing, the working electrode is inserted into the electrolyte and allowed to stand for 30 minutes before measuring the open-circuit voltage. The scan range is then set to open-circuit voltage ± 0.3 V, and the scan rate is 0.001 V / s. The test is then started using 100 ppm HF, 0.1 M HCl, and 0.1 M NaOH aqueous solution as electrolytes, with each sample tested three times.
[0076] It is important to note that multiple measurements should be performed for each sample to obtain at least three sets of valid data. Specifically, in the raw data of the Tafel polarization test, the horizontal axis represents potential, and the vertical axis represents current. Dividing the current by the area of the working electrode yields the current density; taking the logarithm of this density is used as the vertical axis of the Tafel curve. Using the potential of the raw data as the horizontal axis, a "Y"-shaped Tafel curve is obtained (e.g., ...). Figure 13 (a) Figure 14 (a) and Figure 15 (a) As shown in the figure. By extrapolating the anodic and cathodic regions in the curve that conform to the Tafel linear relationship, the corrosion current density and corrosion potential are obtained from the intersection of the tangents. The average value of the three sets of valid data is taken to obtain the representative corrosion current density and corrosion potential of the sample (e.g., Figure 13 (b) Figure 14 (b) and Figure 15 (b) shown).
[0077] First, 100 ppm hydrofluoric acid was used as the electrolyte to perform Tafel polarization tests on the samples. The results are as follows: Figure 13 As shown, in the Tafel polarization test using 100 ppm hydrofluoric acid solution as the electrolyte, the coated aluminum samples all exhibited superior electrochemical protection performance compared to pure aluminum. The corrosion potential of pure aluminum was approximately -1.16 V, while the corrosion potential of the coated samples shifted positively to -0.55 to -0.75 V; simultaneously, the corrosion current density decreased from 17 μA / cm² for pure aluminum. 2 Significantly reduced to approximately 2 μA / cm 2 The positive shift in corrosion potential and the significant decrease in corrosion current density indicate that the composite coating can effectively suppress the electrochemical corrosion process of aluminum substrates in hydrofluoric acid-containing corrosive media, demonstrating that the coating has good anti-corrosion properties.
[0078] Further comparison of the corrosion current density and corrosion potential of samples with different doping amounts of two-dimensional amide polymers revealed that the anti-corrosion performance of the composite coating initially increased and then decreased with increasing two-dimensional amide polymer content, with the best overall protective effect observed at a doping amount of 5% (Example 3). The results indicate that the introduction of an appropriate amount of two-dimensional amide polymer is beneficial to improving the barrier performance of the composite coating. This is mainly because the two-dimensional sheet structure of the two-dimensional amide polymer can form more tortuous diffusion channels in the matrix, i.e., producing a significant "maze effect," thereby effectively extending the penetration path of water molecules, oxygen, and corrosive ions in the corrosive medium to the metal / coating interface and reducing the rate of corrosion reaction. Simultaneously, the high in-plane density and excellent shielding properties of the two-dimensional amide polymer itself also contribute to improving the overall density and interfacial barrier capacity of the coating, thus resulting in an increased corrosion potential and decreased corrosion current density under low doping conditions. However, when the doping amount of two-dimensional amide polymer is too large, the anti-corrosion performance of the coating will decrease: because the high content of two-dimensional sheets is more likely to agglomerate and locally stack in the polyimide substrate, the enhanced interlayer interaction weakens its uniform dispersion in the substrate, resulting in uneven distribution of two-dimensional amide polymer material, local defects or loose structure inside the composite coating.
[0079] Therefore, the introduction of two-dimensional amide polymers can significantly improve the corrosion resistance of composite coatings on aluminum substrates. However, there is a suitable doping range for its reinforcing effect. According to the comprehensive Tafel test results, when the mass fraction of two-dimensional amide polymer doping is 5%, the composite coating has both a high corrosion potential and a low corrosion current density, exhibiting the best corrosion resistance.
[0080] To further evaluate the applicability of the two-dimensional amide polymer-polyimide composite coating of the present invention in a wider range of corrosive environments, in addition to conducting Tafel polarization tests using 100 ppm hydrofluoric acid solution as the electrolyte, 0.1 M NaOH and 0.1 M HCl were further selected as acidic and alkaline corrosive media, respectively, to test the electrochemical protective performance of the composite coating in different chemical environments. The results are as follows: Figure 14 and Figure 15As shown, the test results indicate that under both acidic and alkaline conditions, most aluminum sheet samples coated with the two-dimensional amide polymer-polyimide composite coating exhibit superior corrosion resistance compared to pure aluminum. This demonstrates that the composite coating not only provides excellent protection in hydrofluoric acid-containing media but also effectively protects the substrate in typical acid and alkaline corrosive environments. Further comparison of the Tafel polarization results of samples with different two-dimensional amide doping amounts reveals that the corrosion resistance exhibits a similar pattern to the hydrofluoric acid system, showing an overall trend of initial enhancement followed by weakening. Within the lower doping range, the corrosion resistance of the composite coating gradually improves with increasing two-dimensional amide polymer content; however, as the doping amount continues to increase, the corrosion resistance decreases. In 0.1 M HCl solution, the corrosion resistance of samples with different doping amounts shows a non-monotonic change. The sample with a doping amount of 3% exhibits a relatively high corrosion current density and poor overall protective performance, indicating that lower doping amounts of two-dimensional amide polymer A may not form an effective barrier in strongly acidic, chlorine-containing environments. With further increases in doping concentration, the corrosion resistance of some medium-doped samples improved, with the sample exhibiting the best corrosion resistance at a doping concentration of 7% (see [reference]). Figure 15 When the doping concentration is too high, the protective effect decreases again, which may be related to sheet aggregation and local film defects; while when using 0.1 M NaOH as the electrolyte, the optimal doping concentration is 3% (see...). Figure 14 As can be seen, the optimal doping amount of the two-dimensional amide polymer in the composite coating is affected by the properties of the corrosive medium. The internal structural stability, corrosive medium penetration behavior, and interfacial reaction process of the composite coating vary under different acid and alkali environments, which leads to the fact that the optimal doping ratio is not completely consistent. Specifically, when applying the two-dimensional amide polymer-polyimide composite coating of the present invention, the optimal doping amount of the two-dimensional amide polymer can be selected according to the main corrosive medium involved in the actual application scenario.
[0081] Further analysis, combining the morphological characterization of the two-dimensional amide polymer-polyimide composite coating and the Tafel polarization test results, reveals that the improved corrosion resistance of the two-dimensional amide polymer-polyimide composite coating mainly stems from the enhanced coating-metal interface bonding and the barrier effect of the two-dimensional sheets on the penetration of corrosive media. At the interface between the composite coating and the metal substrate, both the polyimide substrate and the two-dimensional amide polymer filler contain polar functional groups such as carbonyl groups, which can generate strong interfacial interactions with the oxide layer or hydroxylation sites on the metal surface. This interaction helps to improve the adhesion between the composite coating and the metal substrate, reduce the probability of micropores and debonding defects at the interface, and thus inhibit the rapid diffusion of corrosive media along the coating / substrate interface. When the interfacial bonding is weak, moisture, oxygen, and Cl... -Corrosive media are more likely to preferentially penetrate along the interface and further induce local corrosion; however, after the introduction of two-dimensional amides, the more abundant polar groups and stronger interfacial interactions in the composite system can improve the interfacial stability, thus helping to delay the corrosion initiation process.
[0082] When two-dimensional amide polymers are dispersed on a polyimide substrate as high aspect ratio two-dimensional sheet fillers, they can construct more tortuous diffusion paths within the composite coating, exhibiting a typical "maze effect." For water molecules, oxygen molecules, and corrosive ions in the external environment, their penetration through the composite coating to reach the metal surface is no longer a simple linear diffusion process. Instead, they need to constantly change their migration paths, bypassing the two-dimensional sheets of the amide polymer, thus significantly increasing the diffusion distance and transport resistance, and reducing the penetration rate of corrosive media to the metal surface. Simultaneously, the two-dimensional amide polymer sheets can be highly densely stacked, with almost no free volume between layers for small molecules to pass through. The staggered stacking of adjacent layers further blocks effective transport channels. This multilayer structure endows the two-dimensional amide polymer with high barrier properties.
[0083] In summary, the improved corrosion resistance of the two-dimensional amide polymer-polyimide composite coating is not due to a single factor, but rather the result of the combined effects of interfacial enhancement and lamellar barrier effects. The introduction of the two-dimensional amide polymer not only enhances the interfacial interaction between the composite coating and the metal substrate, improving adhesion stability, but also significantly slows down the penetration of water, oxygen, and corrosive ions through the formation of tortuous diffusion channels in the substrate via high aspect ratio two-dimensional lamellars, ultimately achieving the improved corrosion resistance of the composite coating.
[0084] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A two-dimensional amide polymer-polyimide composite coating, characterized in that, Including the following raw materials: polyimide base and two-dimensional amide polymer; The raw materials for preparing the polyimide substrate include: 4,4'-diaminobenzoyl aniline, pyromellitic anhydride, and reaction solvent A; The doping amount of the two-dimensional amide polymer is 1% to 9% by weight, which is the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride, and the two-dimensional amide polymer. The raw materials for preparing the two-dimensional amide polymer include: melamine, 1,3,5-benzenetricarboxyl chloride, calcium hydride, and reaction solvent B.
2. The two-dimensional amide polymer-polyimide composite coating according to claim 1, characterized in that, The doping amount of the two-dimensional amide polymer is 3% to 7% by weight, which is the sum of the contents of the 4,4'-diaminobenzoyl aniline, the pyromellitic anhydride and the two-dimensional amide polymer.
3. The two-dimensional amide polymer-polyimide composite coating according to claim 1, characterized in that, The molar ratio of melamine, 1,3,5-benzenetriformyl chloride, and calcium hydride is 1:1:
3.
4. The two-dimensional amide polymer-polyimide composite coating according to claim 1, characterized in that, The reaction solvent A is one of N,N-dimethylacetamide or N,N-dimethylformamide.
5. The two-dimensional amide polymer-polyimide composite coating according to claim 1, characterized in that, The reaction solvent B is a mixed solution of N-methyl-2-pyrrolidone and pyridine, and the volume ratio of N-methyl-2-pyrrolidone to pyridine is 9:
1.
6. A method for preparing a two-dimensional amide polymer-polyimide composite coating, used to prepare the two-dimensional amide polymer-polyimide composite coating as described in any one of claims 1 to 5, characterized in that, The preparation method of the two-dimensional amide polymer-polyimide composite coating includes the following steps: Preparation of two-dimensional amide polymer: Melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride are mixed sequentially, reaction solvent B is added and stirred, and the reaction is carried out until the reaction system changes from liquid to colloidal; the colloidal substance is washed, purified and dried to obtain two-dimensional amide polymer powder; Preparation of polyimide substrate: Add 4,4'-diaminobenzoyl aniline and reaction solvent A, stir until the 4,4'-diaminobenzoyl aniline dissolves, add pyromellitic anhydride and continue stirring to obtain polyimide substrate solution; The polyimide substrate solution and the two-dimensional amide polymer powder are mixed and stirred to obtain a two-dimensional amide polymer composite polyamic acid solution; the doping amount of the two-dimensional amide polymer is 1% to 9% by weight of the sum of the contents of 4,4'-diaminobenzoyl aniline, pyromellitic anhydride and the two-dimensional amide polymer. The two-dimensional amide polymer composite polyamic acid solution was coated onto a metal substrate and then subjected to thermal imidization treatment. After cooling, a two-dimensional amide polymer-polyimide composite coating was prepared on the surface of the metal substrate.
7. The method for preparing the two-dimensional amide polymer-polyimide composite coating according to claim 6, characterized in that, In the step of preparing the two-dimensional amide polymer, melamine, 1,3,5-benzenetricarboxyl chloride and calcium hydride are mixed sequentially and reaction solvent B is added. The mixture is then stirred at room temperature and pressure until the reaction system changes from a liquid to a colloid. The colloid was washed and purified sequentially with anhydrous ethanol, deionized water and acetone to obtain a washed and purified intermediate product. The washing and purification steps included sequentially performing water bath sonication, centrifugation and collecting the solid, and drying the intermediate product to obtain the two-dimensional amide polymer powder.
8. The method for preparing the two-dimensional amide polymer-polyimide composite coating according to claim 6, characterized in that, The solid content of the two-dimensional amide polymer composite polyamic acid solution is 10% by mass percentage.
9. The method for preparing the two-dimensional amide polymer-polyimide composite coating according to claim 6, characterized in that, The step of thermally imidizing the metal matrix coated with the two-dimensional amide polymer composite polyamic acid solution includes: The sintering temperature of thermal imidization was increased sequentially from room temperature to 70, 100, 150, 250 and 300°C at a heating rate of 5°C / min. Each sintering temperature was held for 1 hour. After cooling to room temperature, the two-dimensional amide polymer-polyimide composite coating was prepared on the surface of the metal substrate.
10. The method for preparing the two-dimensional amide polymer-polyimide composite coating according to claim 6, characterized in that, Before coating the two-dimensional amide polymer composite polyamic acid solution onto the metal substrate, the following steps are also included: cleaning, drying and plasma treatment of the metal substrate.
